The Impact of Human Resource Management Practices on Employees’ Performance: The Evidence from Selected Commercial Banks in Jaffna District. - Vivek, R. (University of Jaffna, 2018)
In the current scenario, Human Resource Management Practises play an important Role in Organization to increase the Employees' Performance. The purpose of this paper is to examine the impact of human resource management (HRM) practices on Employees' performance. If it Managed efficiently and effectively, Human Resource can play an important role in realizing the objectives of the organization, as an integral source. For the purpose of this study data collection was done through the questionnaire and reliability of the items ware confirmed further 184 respondents were selected based on convenient sampling method from managerial and non-managerial staffs from selected most leading Commercial banks in Jaffna District. Statistical Package for Social Sciences (SPSS) was used to analyze the data and statistical tools such as correlation and regression the related variables. The results indicate that HRM practices Recruitment and selection, Training and Development, Compensation and Performance Appraisal have a positive impact on employee‘s performance. Hence that independent variables contribute positively towards change in the dependent variable.
Keywords: hrm practices recruitment and selection; training and development compensation; performance appraisal and employees performance.